Pengaruh Pengembangan Karir, Pendidikan dan Pelatihan Terhadap Kinerja Pegawai Pada Dinas Perhubungan Kabupaten Probolinggo - Hanny Indasari; Khusnik Hudzafidah; Mutinda Teguh Widayanto (Universitas Panca Marga, 2023)
This research was conducted at the Probolinggo Department of Transportation with the aim of knowing the effect of Career Development, Education and Training on Employee at the Probolinggo Department of Transportation. The type of research used is quantitative research with associative approach with Career Development and Education and Training independent variables and Employee performance as dependent variable. The population is gonverment employees in the Probolinggo Department of Transportation with a sample of 67 respondents and the sampling technique used is saturated sampling. Data collection methods used in this study were interviews, questionnaires, and documentation which were distributed to employees at the Probolinggo Department of Transportation. The results showed that career development had a positive and significant effect on employee performance, education and training had a positive and significant effect on employee performance